2014
DOI: 10.1371/journal.pone.0087051
|View full text |Cite
|
Sign up to set email alerts
|

Biological Roles of the O-Methyl Phosphoramidate Capsule Modification in Campylobacter jejuni

Abstract: Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, and the capsular polysaccharide (CPS) of this organism is required for persistence and disease. C. jejuni produces over 47 different capsular structures, including a unique O-methyl phosphoramidate (MeOPN) modification present on most C. jejuni isolates. Although the MeOPN structure is rare in nature it has structural similarity to some synthetic pesticides. In this study, we have demonstrated, by whole genome comparisons and high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 46 publications
3
80
0
Order By: Relevance
“…When both mutants were complemented with their respective, repaired alleles (called CJJ1420 Ϫ /C or CJJ1435 Ϫ /C), the serum resistance returned to levels comparable to that of the wild type. However, mutation of both MeOPN transferases (strain 3479) resulted in enhanced sensitivity over the CJJ1420 Ϫ mutant and showed levels of sensitivity similar to those reported previously for another double transferase mutant (24) and for the mpnC mutant (23).…”
Section: Figsupporting
confidence: 83%
See 4 more Smart Citations
“…When both mutants were complemented with their respective, repaired alleles (called CJJ1420 Ϫ /C or CJJ1435 Ϫ /C), the serum resistance returned to levels comparable to that of the wild type. However, mutation of both MeOPN transferases (strain 3479) resulted in enhanced sensitivity over the CJJ1420 Ϫ mutant and showed levels of sensitivity similar to those reported previously for another double transferase mutant (24) and for the mpnC mutant (23).…”
Section: Figsupporting
confidence: 83%
“…Although van Alphen et al (24) reported that the population of their strain of 81-176 had the CJJ1420 gene in an off configuration, they constructed a double mutant mutated in both putative transferase genes and showed that this mutant was sensitive to complement killing, an observation consistent with earlier work with the mpnC mutant (23). When the variable regions of both MeOPN transferases were sequenced from the population of our version of strain 81-176, CJJ1420 was also in an off configuration, while CJJ1435 was on.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations